1973
DOI: 10.1051/animres:19730106
|View full text |Cite
|
Sign up to set email alerts
|

Effet De La Teneur en Protéines De Rations a Base De Soja Ou De Sésame Sur La Croissance Du Lapin

Abstract: Au cours de 3 expériences successives, nous avons évalué sur un total de 170 lapins en croissance, l'efficacité de régimes à taux protéiques variables. Dans toutes les rations les protéines ont été apportées uniquement par du tourteau de soja (m à z 9 p. 100 de protéines) ou du tourteau de sésame (13 à 25 p. 100 de protéines). Pour les 2 types de protéines la croissance est améliorée jusqu'à un seuil de y-i8 p. 100 de protéines. L'indice de consommation est amélioré avec le soja jusqu'aux environs de 1 8-20 p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

1987
1987
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Studies performed at INRA (Lebas et al, 1973;Colin 1974, 1975 a and and those of Davison and Spreadbury (1975) and Spreadbury (1978) led to confirming the essentiality of these amino acids and the high requirements of arginine, in contrast to the ones observed in poultry. They also suggested that the optimal level of an amino acid depends on the balance with other amino acids and the level of energy in the diet, so the recommendation for lysine is given in grams per 1000 kcal of digestible energy.…”
Section: Introduction: a Historical Perspectivementioning
confidence: 85%
“…Studies performed at INRA (Lebas et al, 1973;Colin 1974, 1975 a and and those of Davison and Spreadbury (1975) and Spreadbury (1978) led to confirming the essentiality of these amino acids and the high requirements of arginine, in contrast to the ones observed in poultry. They also suggested that the optimal level of an amino acid depends on the balance with other amino acids and the level of energy in the diet, so the recommendation for lysine is given in grams per 1000 kcal of digestible energy.…”
Section: Introduction: a Historical Perspectivementioning
confidence: 85%
“…Studies to determine the required levels of amino acids for rabbits began in the 1960s (McWard et al, 1967;Gaman & Fisher, 1970;Cheeke, 1971;Adamson & Fisher, 1971, with those focusing on commercial animals starting in the 1970s (Lebas et al, 1973;Colin, 1975;Davison & Spreadbury 1975;Spreadbury, 1978) and forming the basis of the nutritional recommendations included in the NRC (NRC, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in controlled experimental conditions, a diet containing only 60 g fibre kg −1 dry matter (DM, as acid detergent fibre, ADF) may not induce digestive trouble ( Davidson and Spreadbury, 1975). A similar situation has been observed with diets containing up to 280-300 g crude protein (CP) kg −1 (Lebas, 1973). However, in rabbit-farming conditions, such imbalances lead to a high risk of digestive disorders, and obviously must never be recommended for practical feeding.…”
Section: Introductionmentioning
confidence: 76%